High-speed algorithm for carrier frequency recovery and frame synchronization in QPSK-modulated modems - Sadchenko, A. V.; Kushnirenko, O. A.; Koshelev, Ye. K.; Bondar, V. I. (Technology and design in electronic equipment, 2018)
When demodulating signals in communication systems with QPSK modulation operating in the pulsed mode, the following problems arise: rapid elimination of the reference oscillator phase ambiguity and ensuring reliable frame synchronization for a given noise immunity. In most QPSK modems, the carrier frequency recovery and synchronization recovery tasks are separated and solved with the help of different functional modules, which is not the optimal solution from the point of view of increasing the energy efficiency.In this paper, we propose a fast algorithm for frame synchronization and recovery of the carrier frequency of a QPSK modem using Barker sequences as synchronization signals in conjunction with the coordinated processing.The simulation of the combined circuit is performed, which allows to eliminate the phase ambiguity of the reference oscillation with the simultaneous formation of the frame synchronization signal for various combinations of binary sync codes of the length N = 7.To obtain a reference oscillation, a stable quartz oscillator is used. An external adjustable phase shifter block abruptly changes the phase of the oscillator, and the phase ambiguity, which is multiple of 90°, is eliminated by parallel analysis of all possible rotations of the signal constellation plane in the units, each of which contains a pair of filters matched to the signal distributed over in two quadratures.The timing for the proposed scheme does not depend on the initial phase difference between the received and the initial signal constellations, while the circuit realization of a non-tunable oscillator is much simpler than that for a voltage controlled oscillator.